2002
DOI: 10.1177/10528402012003002
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Findings of Patients With Retinal Ischemia or Embolism

Abstract: Echocardiography frequently identifies lesions of the heart or aortic arch that can act as potential sources for retinal ischemia or embolism. Further studies are needed to evaluate the prognostic and therapeutic relevance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cardiogenic emboli are a very rare cause of CRAO. While atrial fibrillation and left ventricular dysfunction were shown to be the most common cardiac sources, extracardiac sources (mainly aortic and carotid plaques) are associated with CRAO in the large majority of patients 1 . Unfortunately, the source of embolism remains unclear in about 45% of the patients 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiogenic emboli are a very rare cause of CRAO. While atrial fibrillation and left ventricular dysfunction were shown to be the most common cardiac sources, extracardiac sources (mainly aortic and carotid plaques) are associated with CRAO in the large majority of patients 1 . Unfortunately, the source of embolism remains unclear in about 45% of the patients 2 .…”
Section: Discussionmentioning
confidence: 99%